Analisis Kesuksesan Siakadu UNESA Menggunakan Updated Information System Success Model Delone & McLean - Iqbal, Mohamad; Safitri, Eristya Maya; Wulansari, Anita (Universitas Labuhanbatu, 2024)
The development of Information Systems is currently an important element for higher education institutions to support business processes in the world of Education. Similar things are also implemented in Unesa or Surabaya State University Applied SIAKADU or integrated academic Information System. SIAKADU is a site-based Scholastic data framework that can be accessed easily, anytime and anywhere, as long as anything is connected to a web connection. The purpose of this test is to survey whether Delone and McLean's Refreshed Data framework achievement Model can really be applied to the Incorporated Scientific Data Framework at Surabaya State University, as well as to distinguish variables from this model that have an impact on the progress of the framework. . This exploration technique is one of the methodologies used to dissect the results of a data frame. This exam included a fixed proportional irregular exam involving 391 respondents who were active students at Surabaya State University. There are several factors that affect the success of an integrated academic information system when viewed from the results of the analysis that has been done. Actual use, the intention of the perpetrator, the quality of Service, and the quality of information are some of the factors in question. Furthermore, the intention of users to use the integrated academic Information System is significantly influenced although not significantly by user satisfaction and system quality.